Evaluation of the structure and processes of administrative areas in hospitals: a case study in a social health organization (Research, Society and Development, 2022)
The objective was to identify the infrastructure conditions and operational flows of the administrative services and to characterize the administrative services in terms of staff, activities carried out and processes described. Qualitative and descriptive study which proposes to understand a phenomenon, describing the variables that compose it and interfaces that characterize and particularize it. When evaluated in percentage terms, they presented a positive evaluation of less than or equal to 50% by criteria: Infrastructure (78%), Management (60%), operational technician (77%) and Safety and Risk (62%). And when greater than 50%, with a negative evaluation, we have the evaluation by criteria: Infrastructure (22%), Management (40%), operational technician (23%) and Security and Risk (38%). The study suggests that this exposed monitoring presents itself as a successful tool for evaluating the structure and processes of the administrative areas in hospitals, capable of identifying the infrastructure conditions and operational flows of the administrative services, of characterizing the administrative services in terms of the team, activities carried out and processes described and propose process indicators and respective critical analysis based on the identified causes, contributing to the planning and preparation for action, suggesting that it is advisable to replicate the study in other hospital units as a tool that enhances management.